Molecular Marker Confirmation for Member of Anopheles barbirostris Van Der Wulp 1884 in Different Localities - Tri Baskoro Tunggul Satoto (Indonesian Journal of Biotechnology, 2012)
Vector and non-vector forms of Anopheles barbirostris have been recognized in Indonesia. However, because of their similarity in morphology, they were considered to be a single species. This information has led to the hypothesis that Anopheles barbirostris is a complex of species, which are morphologically indistinguishable from each other by ordinary methods. Objectives of the research was to identify the member of Anopheles barbirostris by PCR Assay. Samples were taken from two localities in Java, two in Sulawesi, two in Flores Indonesia, one from Thailand, one from China. The study was to develop a PCR-based technique of rDNA ITS2 region. Results showed that there are at least four species within the Anopheles barbirostris population studied, namely Anopheles barbirostris species DW, DX, DY and DZ. The length of the sequence amplified for species W, species X, species Y, and species Z were 339bps, 247bps, 165bps. and 157bps, respectively. Verification of the method was carried out with 270 mosquitoes from eight different field-collection sites using various sampling methods. Samples collected from Singaraja-Flores were identified as species W and X. All specimens collected from human bite outdoors were identified as species X; this species showed to be predominant among indoor light trap, indoor human bite and indoor resting collections Samples from Reo-Flores were identified as species W and X. All specimens from Manado and Palopo in Sulawesiwere identified as species Z. Similarly only species Y was found in samples from Thailand, while specimens from Salaman and Jambu in Java were identified as species W or species X. These species-specific molecular markers for the Anopheles barbirostris, complex appear to be reliable over a wide geographical area. However, larger number of samples is still needed from throughout the range of this species.Key words: Anopheles barbirostris, ITS2, PCR, Specific primer diagnostic